The Effect of Parental Absence on Children’s Literacy Development: A Case Study of a Fourth-Grade Elementary School Student - Petra Kristi Mulyani (Universitas Islam Negeri Walisongo Semarang, 2022)
The research analyzed the parental role in the literacy development of a fourth-grade Midwestern elementary school student in the United States of America. The subject selection was based on the beginning of the year assessment, which showed an early second-grade literacy level. Data were collected through observation and in-depth interviews with the homeroom teacher, reading specialist, and the subject for one semester. The observation notes, and interview transcriptions were coded. The four emerging themes were the subject’s literacy level, parental background, the caregiver’s literacy belief and behavior, the home literacy environment, and the subject’s literacy interest. The analysis showed that parental absence affected the subject’s lack of motivation in facing academic challenges and literacy difficulties. Low motivation led to low academic achievements, including literacy. The caregiver, which was the grandfather, did not display his parental role in reinforcing the subject’s literacy. A home literacy-rich environment was not created. The caregiver did not expose the subject to literacy-related activities at home. Meaningful conversation on literacy activities and achievements was not made between the caregiver and the subject, which was suggested to be the factor that caused the subject’s difficulties in processing and delivering information. The limited parental support by the caregiver on the subject’s literacy activities and resources was analyzed to be the instrumental factor that caused the subject’s difficulties in reading and writing.